Evaluation Of Toraks USG Implementation With Indication Of Pleural Effusion Minimally In Dr. H. A. Rotinsulu Hospital Bandung - Halimatus Sa’diah; Gando Sari; Januar Sudarmono; Sarengat Sarengat (SANITAS: Jurnal Teknologi dan Seni Kesehatan, 2017)
This study aims to describe and evaluate the examination procedures, scanning techniques and thoracic ultrasound results with indications of pleural effusion minimally. This study was used 3 patients at Lung Hospital of dr. H. A. Rotinsulu Bandung. The 3 samples were tested using MEDISON (Accuvix V20) ultrasound type V20 Prestige. The examination technique uses a convex transducer with a frequency of 3.5 MHz To obtain the results of the image of pleural effusion minimally was performed with longitudinal and transverse section on intercostals scanning. The patient's position was sat with legs crossed on the examination table with the arm on the side of ​​the examined section was placed overhead so that the intercostals space can be opened more widely. The results of the on thoracic ultrasound image can be seen from the ecogenicity, ecostructure and fluid volume